Pelatihan Mind Mapping K3 di Pondok Pesantren Al-Ishlah Bandar Kidul Kota Kediri Dalam Rangka Mencegah Penularan Covid-19 - Nurlina, Nila; Yunus, M; Mekar Bisono, Rahayu; Irawan, Dani (Universitas Nusantara PGRI Kediri, 2021)
Islamic boarding school is a unit of educational institution that have functions as a Islamic education. This program partner is Pondok Pesantren Al-Ishlah Bandar Kidul at Kediri City. This Islamic boarding school has hundreds of students from various regions in Indonesia and has several activity areas such as halls, classrooms, canteen, beds, ablution places, and bathrooms. These places are public places that are touched by many people. Therefore, in order to avoid accidents and occupational diseases, it is necessary to map the implementation of Occupational Health and Safety (K3) before the students begin their activities. In this program, the students were given training on K3 and made mind mapping in the boarding school environment. It aims to make the students aware of and understand the importance of implementing K3 in their daily life. In addition, this program aims to prevent the transmission of Covid-19. The steps for implementing this community service program are observation, formulation of priority problems, training design, training, and evaluation. The results obtained from this program are that students understand K3 well and able to implementation of K3 through mind mapping.